Analisis Konten Isu Kekerasan Berbasis Gender Online (KBGO) di Instagram @purplecode_id - Gusti Ayu Made Kayika; Syafrida N. Febriyanti (Public Inspiration : Jurnal Administrasi Publik, 2025)
The 324 victims of GBV were mostly aged 18-25, with complaint data also including reports from 256 male victims (SAFEnet, 2024). As a non-physical form of gender-based violence factored by digital power relations dominated by anonymity and difficult to trace perpetrators, this violence can occur with or without internet transmission. Through the Instagram account @purplecode_id, the organization actively campaigns for digital rights by promoting the idea of a feminist internet as a safe space for expression, championing information accessibility, advocating for knowledge about GBV, and addressing privacy for women, children, and marginalized groups. Using content analysis as a qualitative research method, the study aims to interpret each piece of content on the @purplecode_id Instagram account as a symbol of a social movement relevant to the issue of GBV in Indonesia. Interpreting the context within GBV content is useful for in-depth explanations of complex issues, incorporating language composition and communication styles that are more easily understood by Instagram audiences. The form of Instagram content analyzed was in the form of 6 posts on a page (carousel) of Instagram content @purplecode_id which contained information about issues of KBGO, digital security, freedom of expression, and privacy as a communicative, relevant, and unique campaign.